Psychophobia and its Cure: An existential phenomenological perspective (Existential Analysis: Journal of the Society for Existential Analysis, 2025)
This paper examines psychophobia, including society's fear of extreme mental states, using ideas from existential psychoanalysis. It critiques the medicalisation of mental health, emphasising iatrogenic harm and the assault on interiority. Advocating for psychophobia-free phenomenological therapeutic approaches, it highlights the transformative potential of authentic human connection and radical agency.
Keywords: Psychosis; psychophobia; existential psychoanalysis; Laing; McDonaldisation